Association of Risk Factors of Burn with Mortality in Children: A Retrospective study (Medical Forum Monthly, 2024)
Objective: A Retrospective study has been devised to study the risk factors associated with the burns patients and to determine the potential complications experienced by those patients.Study Design: Retrospective study.Place and Duration of Study: This study was conducted at the Burns Centre, Civil Hospital Karachi from 1st January 2015-30th September 2015.Materials and Methods: A total of 227 patients have been employed in the study. Purposeful sampling has been used to select the sample size for the specific study. The data collection procedure for the study was completed within 9 months. Children specifically from Karachi city from birth till 12 years have been entailed in the study.Results: With the exception of 1 suicidal cause of burn, the rest 226 were accidental in nature. Only 3.1% (7) patients burnt outdoor, 0.4% (1) burnt on a ship whereas 96 % (218) patients were burnt indoors. Amongst the total admissions 89% (202) had 10-50% total body surface area burnt (being the most common category), whereas 9.7% (22) had <10% TBSA burnt while only 1.3% (3) had >50% TBSA burnt. The percentage of TBSA burnt is significantly associated with mortality (p=0.003), with 92% (59) deaths having TBSA 10-50%.Conclusion: TBSA% is most important single predictor for mortality among children with burn.